Data analysis for performance index of plate heat exchanger filled by ionanofluid-oil: parallel versus counterflow - Ishrat Zahan; Rehena Nasrin; Nusrat Jahan Jakia (Scientific Reports)
Abstract Plate heat exchangers ensure their continued relevance and adaptability in meeting modern energy, environmental, and industrial demands. Innovations in this area significantly improve energy efficiency, reduce environmental impact, and enhance industrial processes. However, the ionanofluid significantly enhanced the thermal conductivity and heat transfer coefficient compared to conventional fluids. This study focuses on a three-chambered parallel plate heat exchanger (PHE) using cold ionanofluid (a mixture of graphene as nanoparticle and 1-ethyl-3-methylimidazolium thiocyanate ([C2mim][SCN]) as ionic liquid) in the top and bottom channels and hot oil in the middle channel. It aims to determine the most effective configuration for performance index (η) and energy efficiency, given the unique properties of ionanofluid. The governing equations of Navier–Stokes and energy balance are solved numerically using the finite element method. The impact of different Reynolds numbers (Re) and solid concentrations (ϕ) of nanoparticles on the fluid velocity and temperature fields is observed, and various related parameters are calculated. A comprehensive data analysis is conducted using the surface response method, including ANOVA, sensitivity analysis, and optimization testing. The counter and parallel flow designs achieve approximately 76.23% and 70.07% thermal enhancement at Re = 1, respectively. The optimal performance index occurs at (Re = 1, ϕ = 0.025), chosen to maximize predicted η (= 33972.3) and actual η (= 34020.03). The results indicate that the counterflow configuration consistently outperforms the parallel flow configuration regarding heat transfer efficiency. The counterflow configuration exhibited superior overall performance and provided a more uniform temperature distribution across the PHE. This research offers important insights into the application of ionanofluids in heat exchangers by comparing both parallel and counterflow setups. The study demonstrates high R2 values for the response function, highlighting its significance, and suggests practical implications for the optimization of heat exchanger designs in industrial settings.